Analyse critique de Régime disciplinaire des Agents et Cadres du personnel Administratif de la Directions Générale de douanes et Accises; cas de Direction Province Orientale / Kisangani en République Démocratique du Congo: - BOKUBALI LINZABE, Jean Oscar (IJRDO - Journal of Business Management, 2023)
The problem addressed in this article is to do a critical analysis of the disciplinary regime applicable to the administrative staff and executives of the Customs and Excise Branch, Eastern province of Kisangani.The administrative staff of this public company which is a financial authority like the Directorate General of Taxes (DGI) in the acronym and the DGRAD is at the center of our research because of its belonging and its professional conscience must be established with good social  relation  with  one  the  others and especially work while respecting the disciplinary regime and the legal texts that are in force; Congolese working code, collective agreements, code of good conduct of agents and civil servants of the Congolese state, etc.The main objective is to provide critical trial as to the application  of  the measures, and  disciplinary  sanctions  imposed  on  the  agents  and  executives, the administrative staff of the Customs Directorate and Executives of the East Dismembered Province, working in Kisangani. Bring them to become aware of the unjust sanctions and disciplinary measures  outside  the  law  imposed  on them by the employer. Pushing and getting them to defend their rights that are violated by the employer in  the  mobilization  process  and  maximization  of public funds.Building on the systematic method and thinking of LECLERQ on the choice of social science method, must depend on the object of researcher's research and purpose: "A well-conducted investigation must solve a large  number  of difficulties and make all the means of information has". The study leads to the following results: the disciplinary regime applicable to administrative staff and executives of the Customs and Excise Branch "DGDA / Kisangani" is mixed, does not respect the texts, laws and violent the law and procedure disciplinary sanctions inflicted on state career staff and careerIt is a source of social conflicts between the employer and the employees and created a lot of stress and somatic disease (voltage, hypo and hypertension, paralysis and sudden death ). The disciplinary sanctions sometimes inflicted on certain arguments and administrative frameworks are of origin, political, tribal ethnic, revenge and can numerous are of an administrative nature.DGDA agents and executives are aware of their suffering, and see their right influenced for the boss (employers).Thus, the “socio-termitary”, a notion in sociology born of the Marxist social class theory focused on the year of conscience of the administrative staff of the DGDA / Kisangani staff is the best appropriate to regulate, regulate The disciplinary regime and apply properly, without a state of mind the sanctions imposed on the agents and executives of the said undertaking.